Acute effect of intra-set static stretching on antagonists versus passive interval on the performance of maximum repetitions of agonists in leg extension machine - Souza, Priscila Alves de (2020)
The aim of this study was to investigate the acute effect of intra-set antagonist static stretching (hamstrings) on the performance of maximum repetitions of knee extensors adopting muscle endurance training zone. The sample consisted of 15 healthy male volunteers with experience in strength training (23.7 ± 4.3 years, 81.9 ± 15.0 kg, 1.8 ± 0.1 m). Two experimental protocols were conducted: protocol without static stretching (PT) and antagonist stretching protocol (PAA) in the knee extension exercise. The results showed that there was no difference between protocols or interactions between protocols and sets in maximum repetitions performance (PT, set1 – 21.3 ± 3.4; set2 – 16.1 ± 1.9; set3 – 13.5 ± 1.3 / PAA, set1 – 21.0 ± 2.0; set2 – 16.7 ± 2.6; set3 – 13.7 ± 2.2) (p ≤ 0.05) (p ≤ 0.05). Therefore, antagonist static stretching does not influence performance of maximum repetitions of knee extensors over multiple sets focused on muscle endurance.